Crisis Management in Norwegian Nursing Homes During the Covid-19 Pandemic: Pragmatism and Performativity - Martin S. Krane; Cathrine Arntzen; Laila Tingvold; Jill-Marit Moholt (Scandinavian University Press (Universitetsforlaget), 2023)
Background: The outbreak of the Covid-19 pandemic in early 2020 imposed a severe crisis on nursing homes in Norway. Despite criticism in evaluations pointing to inadequate preparedness, nursing homes managed to keep infection and mortality rates low. Enhanced knowledge of crisis management in the aftermath of a crisis is important for preparedness and future crisis management and can contribute to ensuring sustainable healthcare and nursing services when the next crisis arises. Aim: To explore how nursing home managers performed crisis management during the first eight months of the Covid-19 pandemic. Method: Case studies at five Norwegian nursing homes, utilising thematic qualitative content analysis of interviews. Results: Findings indicate that nursing home managers responded swiftly, implementing creative solutions in close collaboration with staff. They performed pragmatic and performativity-sensitive crisis management, and this may have been a factor contributing to resilience in the Norwegian healthcare sector throughout the first phase of the pandemic. Conclusion: This study contributes to an enriched understanding of how, through performativity-sensitive pragmatic crisis management, experienced and professional healthcare managers contribute to robust, resilient and sustainable Norwegian nursing homes.